PENGARUH LEVERAGE, UKURAN PERUSAHAAN, KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di BEI periode 2014-2016) - Dhea Tirta Ayu Pravesty, 14.05.52.0083; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2018)
This study to examine the effect of leverage, company size, quality audit and comittee audit of tax avoidance on manufacturing companies listed in Indonesia Stock Exchange (BEI). The sample used in this research is manufacturing compenies listed in Indonesia Stock Exchange (BEI) 2014-2016 based on predefined criteria and sample selected were 74 company. Purpose sampling and testing this hypotesis using multiple linear regresion analysis. In this study the variables firm size, quality audit and comittee audit has no affect tax avoidance. While the variable leverage affects tax avoidance. Keyword : leverage, firm’s size, quality audit, comittee audit and tax avoidance